The maternal lifestyle in pregnancy: Implications for foetal skeletal muscle development - Haijun Sun; Meixia Chen; Jialong Liao; Linjuan He; Boyang Wan; Jingdong Yin; Xin Zhang (Wiley, 2024)
Abstract The world is facing a global nutrition crisis, as evidenced by the rising incidence of metabolic disorders such as obesity, insulin resistance and chronic inflammation. Skeletal muscle is the largest tissue in humans and plays an important role in movement and host metabolism. Muscle fibre formation occurs mainly during the embryonic stage. Therefore, maternal lifestyle, especially nutrition and exercise during pregnancy, has a critical influence on foetal skeletal muscle development and the subsequent metabolic health of the offspring. In this review, the influence of maternal obesity, malnutrition and micronutrient intake on foetal skeletal muscle development is systematically summarized. We also aim to describe how maternal exercise shapes foetal muscle development and metabolic health in the offspring. The role of maternal gut microbiota and its metabolites on foetal muscle development is further discussed, although this field is still in its 'infancy'. This review will provide new insights to reduce the global crisis of metabolic disorders and highlight current gaps to promote further research.